Mill : Founders of Modern Political and social thought - Rosen, F. (United Kingdom : Oxford University Press, 2013)
"Frederick Rosen presents an original study of John Stuart Mill's moral and political philosophy, which explores the main themes of his writings--particularly those that emerge from the two major works, System of Logic (1843) and Principles of Political Economy (1848). From these, Mill developed the more widely-read later essays, On Liberty (1859), Utilitarianism (1861), Considerations on Representative Government (1861), and The Subjection of Women (1869). He was one of the greatest thinkers of the nineteenth century, and attempted to understand the political as well as intellectual struggles of his time, including those between capitalism and socialism, liberty and despotism, and Christianity and secular forces (particularly the sciences) that seemed to undermine religious belief. Rosen examines Mill's complex relationships with other contemporary thinkers (such as Jeremy Bentham, James Mill, Auguste Comte, George Grote, and Harriet Taylor Mill), and his philosophical sources, including Socrates, Plato, Aristotle, Hobbes, Locke, and Hume; and goes on to illustrate Mill's influence on subsequent philosophers, logicians, and economists. Rosen considers Mill's approaches to the study of active character and happiness in his work on logic and in the study of political economy, from which new interpretations of his ideas of liberty, justice, equality, and utility follow. Many of the debates with which Mill was engaged remain part of contemporary life, and Rosen's book is a guide for exploring and resolving them. Mill's ideas, his arguments, and the versions of utilitarianism and liberalism that he developed have created a humane, civilising philosophy for our times."--Publisher's website.
Introduction -- [pt.] I. System of logic. A Socratic moment : truth, liberty, and democracy -- The method of reform : Mill's encounter with Bentham and Coleridge -- Psychology, character, national character, and the science of politics -- [pt.] II. The spell of Comte. A dialogue concerning philosophy -- The mature Mill --[pt.] III. Principles of political economy. The circle of liberty -- The journey to socialism : from liberty and representative democracy to co-operation -- From co-operation to socialism -- Justice and private property in the Principles and 'Chapters on socialism' -- Distributive justice in Utilitarianism -- God and the religion of humanity -- Conclusion : liberty and despotism in The subjection of women.
Includes bibliographical references (pages 287-301) and index.
Keywords: Mill, John Stuart, -- 1806-1873.; Mill, John Stuart, -- 1806-1873.; Mill, John Stuart, -- 1806-1873.; Mill, John Stuart